2007
DOI: 10.1007/s10705-007-9100-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of soil organic matter on indigenous soil N supply and wheat productivity in semiarid sub-tropical India

Abstract: A field experiment was conducted on a loamy sand soil for six years to quantify the effect of soil organic matter on indigenous soil N supply and productivity of irrigated wheat in semiarid sub-tropical India. The experiment was conducted by applying different combinations of fertilizer N (0-180 kg N ha -1 ), P (0-39 kg P ha -1 ) and K (0-60 kg K ha -1 ) to wheat each year. For the data pooled over years, fertilizer N together with soil organic carbon (SOC) and their interaction accounted for 75% variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The organic N pool size regulates N mineralization rate in many soils (Wang et al, 2001, O'Connell et al, 2003, Li et al, 2008) despite that some studies reported that the C/N ratio (Springob and Kirchmann, 2003), or the amount of labile soil components may be better predictors (Mishra et al, 2005). Apparent mineralization assessed by the balance approach had been observed to be curvilinearly‐correlated to soil organic C with a net release of 4.8 kg N Mg −1 organic C in some subtropical Indian soils (Benbi and Chand, 2007). The ANN model developed for pampean agroecosystems predicted a mean ANMH of approximately 8 kg N Mg −1 organic N, a much lower mineralization rate, for these soils with a mean C/N of approximately 10 for soil organic matter (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The organic N pool size regulates N mineralization rate in many soils (Wang et al, 2001, O'Connell et al, 2003, Li et al, 2008) despite that some studies reported that the C/N ratio (Springob and Kirchmann, 2003), or the amount of labile soil components may be better predictors (Mishra et al, 2005). Apparent mineralization assessed by the balance approach had been observed to be curvilinearly‐correlated to soil organic C with a net release of 4.8 kg N Mg −1 organic C in some subtropical Indian soils (Benbi and Chand, 2007). The ANN model developed for pampean agroecosystems predicted a mean ANMH of approximately 8 kg N Mg −1 organic N, a much lower mineralization rate, for these soils with a mean C/N of approximately 10 for soil organic matter (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Soil organic matter (SOM) and various physical properties are important indicators of soil quality and play an important role in the soil functionality of production (Shukla et al, 2006;Benbi and Chand, 2007). Cavalieri et al (2009) reported that dynamic properties such as soil aeration, aggregation, bulk density and water transmission have a greater impact on soil physical quality in the surface layers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there are studies from temperate regions which have also reported a strong positive impact of the SOC pool on agronomic yields, including those from Australia(Cotching et al 2002;Farquharson et al 2003), Relationship between grain yield and soil organic carbon concentration in a cambisol, New Delhi, India (Redrawn fromKanchikerimath and Singh, 2001) Influence of soil organic carbon concentration on grain yield of wheat with and without fertilizer and on productivity (redrawn fromBenbi and Chand 2007) …”
mentioning
confidence: 99%